Meningkatkan Hasil Belajar IPA menggunakan Model Pembelajaran Problem Based Learning (PBL) - Ayu Asih Wiranti (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The purpose of this research is to improve student learning outcomes by using a problem-based learning model (PBL), to increase the learning activity of science through the application of learning problem based learning (PBL) model. This research focuses on the problem of how students' science learning outcomes can be improved. The method used by the study document is research by collecting and analyzing data from pre-existing researches. This study uses document studies of previous research results or better known as meta-analysts. Meta-analysis is a review of some research results in similar problems in which the summary of the results of the study was made quantitatively. Data collection in this research is done by browsing the journal in some electronic media such as a digital library, internet, and library journal collection. A journal search is done through Google Scholar. The purpose of this research is to know the effect of the learning-based learning problem model in science subjects in elementary school. Results of data obtained from several research sources published in several journals then analyzed and concluded. The results of this study indicate that the approach of learning the problem-based learning model can improve the learning outcomes of science. The results of this study indicate if there are differences in the results of science learning between students who use a problem-based learning model with students who use the conventional learning model.